Harris Heel View is Inadequate to Visualize Screw Prominence of the Medial Calcaneus: A Case Report and Cadaveric Evaluation. Issue 3 (12th July 2020) - Hadeed, Michael M.; Jennewine, Brenton R.; George, Jose; Yarboro, Seth R.
Abstract : Case: A 58-year-old man sustained multiple right foot injuries during a motor vehicle accident that included a calcaneus fracture requiring open reduction and internal fixation (ORIF). The procedure was complicated by a prominent implant inferior to the sustentaculum, which necessitated a return to the operating room. Commonly used fluoroscopic views do not adequately image this area. A cadaveric study was undertaken to identify the optimal 2-dimensional fluoroscopic view that evaluates prominent implants at the medial calcaneus. Conclusion: The sustentaculum tunnel view gives a reliable image of prominent medial implants, and use of this technique may limit complications after calcaneus ORIF.